Assessment of aggressive potential of breast carcinoma in patients of different reproductive periods - Yurchenkova, Karina V.; Smolyakova, Raisa M.; Shpadaruk, Katsiaryna M.; Andreeva, Irina N. (Journal of the Belarusian State University. Ecology, 2020)
The study found that patients with breast cancer during the active reproductive period had a decrease in the blood content of estradiol (37,5 %) and progesterone (25 %). In patients of the postmenopausal period identified hormonal imbalance,characterized by a more pronounced (100 %) increased levels of estradiol and progesterone in the blood on the background of lowering of the content of luteinizing and follicle-stimulating hormone 50 % and 75 % of the patients respectively, and improvement in 64 % of cases the concentrations of prolactin. In the group of patients of the active reproductive period, an increase in the content of luteinizing hormone was observed in 37,5 %, follicle – stimulating hormone – in 12,5 %, andprolactin – in 25 % of cases. The content of luteinizing hormone in the blood was directly dependent on the concentration of follicle-stimulating hormone (p
Keywords: breast cancer; hormones; hormonal regulation; radioimmunological method; menopause